SISTEM INFORMASI PENDAFTARAN SISWA BARU SMA/ SMK SEKOTA PALANGKA RAYA BERBASIS WEBSITE - Jadiaman Parhusip; Widiatry -; Pendi - (IIB Darmajaya, 2018)
Today, many of schools still use the same old way to process students’ registration. This kind of way is obliged the students who want to enroll as new students in a certain school to come to its physical building. They have to be there to register or find some information about registration requirements, registration dates, test dates, and other possible information. This makes the students need to provide certain time and cost. This problem needs a system to help both students and school authorities to register and manage data of the new students. This information system uses certain phases to identify the problem which later become the reason of why this system is conducted. When conducting this information system, the researcher collects the data using Waterfall method based on Sommerville reference which has five phases such as analysing data needed, designing system, composing programme code, testing programme, applying program and maintaining. This system is designed and modelled the data using DFD and ERD. Besides, this system also uses PHP and XAMPP.This data which consists of data and bundle of new students can be accessed by the administrators (the system’s organizer), the school administrators, the new students, and other visitors. This system offers features that can be freely accessed such as search school, help, account register, school schedule, school profile, manage students’ data, and announcement. This design is tested by Black Box Testing to observe the testing result of each menu and to check functions of the software. Keywords : Information system, new students registration, website